FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGELOLAAN BANK SAMPAH DI KECAMATAN WERU KABUPATEN CIREBON TAHUN 2024 - Dewi Ratnawati; Cucu Herawati; Muslimin Ali; Nisa Karamika Unang Dede (Rena Cipta Mandiri, 2026)
Waste bank is one of the strategies for implementing 3R (reduce, reuse, recycle) in waste management at the source at the community level. Three main factors related to waste bank management, namely community participation or role, the role of the government, and adequate infrastructure. The purpose of this study is to determine the factors related to waste bank management in Weru District, Cirebon Regency in 2024. This study uses quantitative research with a cross-sectional design. The population in this study are waste bank customers who have certain qualities and characteristics determined by the researcher. The sample in the study was 40 samples. The sampling technique was total sampling. The results of the study showed that 20 respondents (50%) had poor waste bank management, 22 respondents (55%) with poor community roles, 24 respondents (60%) with poor government roles and 21 respondents (52%) had poor infrastructure. The results of the chi square test show that the role of the community (p=0.022), the role of the government (p=0.021), infrastructure (p=0.010), have a significant relationship with waste bank management.